Electrically Coupled Folded Arm Resonators with the Feedline Patch Antenna for Spurious Harmonic Suppression and Bandwidth Improvement - Alkhafaji, Mohammed Kadhim (Iraqi Journal for Electrical and Electronic Engineering, 2020)
This paper presents a new design of the filtering antenna with a quasi-elliptic function response. The basic structure of the proposed filtering antenna is consists of a four-folded arms open-loop resonator (OLR). The proposed filtering antenna is simulated, improved and, analyzed by using 3D Computer Simulation Technology (CST) electromagnetic simulator software. The design has good spurious harmonic suppression in the upper and lower stopbands. The Insertion Loss of the proposed filtering antenna IL=0.2 dB and the Return Loss RL= -25.788 dB at the center frequency fo=5.75 GHz. The passband bandwidth which is relatively wide, and equal to 0.793 GHz. The microstrip filtering antenna circuit shows good design results compared to the conventional microstrip patch antenna. The filtering antenna design circuit with etched ground plane structure also has good design results compared to the filtering antenna design which has a complete ground plane structure.